2007
DOI: 10.1136/thx.2007.078980
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fibre type shifting in the vastus lateralis of patients with COPD is associated with disease severity: a systematic review and meta-analysis

Abstract: Background: Skeletal muscle dysfunction is a common feature in chronic obstructive pulmonary disease (COPD) which is associated with intrinsic muscular abnormalities. One of the most consistently reported alterations is a shift from fibre type I to II in the vastus lateralis of these patients. Surprisingly, the relationship between this shift and the severity and phenotype of COPD remains unclear. A study was conducted to determine whether vastus lateralis muscle fibre type proportions are associated with COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
176
6
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(210 citation statements)
references
References 37 publications
15
176
6
3
Order By: Relevance
“…It should be noted, however, that inactivity may act as a significant confounder when observing quadriceps dysfunction as an effect of smoking. Further studies are needed to explore whether the fibre type switch from oxidative type I fibres to anaerobic type II fibres reported in advanced COPD [38] occurs earlier in the disease process as a consequence of physical inactivity interacting with systemic effects.…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…It should be noted, however, that inactivity may act as a significant confounder when observing quadriceps dysfunction as an effect of smoking. Further studies are needed to explore whether the fibre type switch from oxidative type I fibres to anaerobic type II fibres reported in advanced COPD [38] occurs earlier in the disease process as a consequence of physical inactivity interacting with systemic effects.…”
Section: Significance Of the Findingsmentioning
confidence: 99%
“…A subsequent study by Maltais and colleagues (1999) confi rmed a shift toward type II fi bers and a reduction in the proportion of type I fi bers in the vastus lateralis muscles of patients with severe COPD. Recent meta-analysis has revealed that the proportion of type I fi bers in the vastus lateralis muscle correlates with FEV 1 , FEV 1 /forced vital capacity (FVC) and the body mass index (BMI) in patients with moderate to severe COPD (Gosker et al 2007b). Although the exact functional consequences of this fi ber type redistribution remain under investigation, the fact that type II fi bers are fatigue-prone suggests that an increased proportion of type II fi bers might be an important factor in increased leg muscle fatigability and reduced endurance.…”
Section: Fiber Type Shiftmentioning
confidence: 99%
“…26 and reductions in peroxisome proliferator-activated receptors (involved in mitochondrial biogenesis). 43 Gosker et al 21 recently confirmed that the severity of COPD is associated with reductions in the proportion of type I fibres. The aforementioned factors together with the finding that lactic acidosis occurs earlier during exercise in COPD patients compared with healthy subjects, 33 may partly explain why COPD patients fatigue quicker and experience exercise intolerance.…”
Section: Skeletal Muscle Dysfunctionmentioning
confidence: 74%
“…21,34,47 A shift in distribution from slow to fast twitch fibres gives rise to altered activities of key oxidative and glycolytic enzymes 62 that may decrease oxidative capacity and increase the risk of developing insulin resistance. 48 Whether resistance training exacerbates this phenotype switch, decreasing functional and oxidative capacity further, or maintains the status quo, has not been determined in COPD patients.…”
Section: Resistance Training and Molecular Adaptations In Skeletal Mumentioning
confidence: 99%